Stability Analysis of Surrounding Rock in the Diversion Tunnel at the Xulong Hydropower Station based on RFPA3D and Microseismic Monitoring - Hongjian Qian; Zhou Tan; Biao Li (Applied Sciences, 2022)
To study the surrounding rock stability of the excavated geologically weak section of the #2 diversion tunnel in the Xulong Hydropower Station, a quasi-3D numerical model was built using the Realistic Failure Process Analysis (RFPA3D) system to simulate the damage and failure process consisting of crack initiation, growth, and penetration in the rock mass after tunnel excavation, and reveal the instability failure mechanism inside the rock mass. Moreover, the microseismic monitoring technology was employed to delineate potential danger areas in the surrounding rock of the tunnel and explore possible instability failure modes. Results indicate that the surrounding rock of the tunnel profile failed as different degrees during the excavation process, most obviously near the vault and corners of the side wall, where tensile failure predominated. As the excavation proceeded, microseismic events increased gradually at the vault and corners of the side wall, and the energy from acoustic emissions accumulated steadily, thus raising the possibility of collapse and rock bursts in this area. The research results can provide technical support for the construction of the diversion tunnel project in the Xulong Hydropower Station and serve as a guide for the construction of similar geologically weak underground projects.